The effect of illness perception on physical health-related quality of life promotion in multiple sclerosis (MS) patients attending peer support groups - Jadid Milani, Maryam; Ashktorab, Tahereh; Abed Saeedi, Zhila; Alavi Majd, Hamid (Archives of Advances in Biosciences, 2012)
Illness perception influences patients’ decision to adopt effective behavior and achieve positive results such as adapting with the disease and improving functionality, and the interventions that increase illness perception can promote health. This study aimed to investigate the effect of illness perception on the physical health-related quality of life of MS patients attending peer support groups. This study with a quasi-experimental before-and-after design included 33 MS patients in three groups: male-only(n=10), female-only(n=11) and one with both males and females (mixed, n=12) that selected by convenience sampling Participants were required to attend 8 weekly sessions comprising 2 hours each. Instruments used to assess physical health related quality of life and illness perception were the physical health section of "Multiple Sclerosis Quality of Life Inventory (MSQLI)" and "Revised Illness Perception Questionnaire(IPQ-R)" respectively, which were completed by participants before and after attending the group sessions. The results showed that although illness perception of MS patients attending peer support groups did not show a significant increase, physical health significantly improved(p=0.001). Attending peer support group increased illness perception in the mixed group(p=0.01) and elevated physical health in men only and mixed group (p=0.03 for the mixed group and p=0.04 for men only group). Regression analysis showed a significant relationship between MS and physical health with efficacy of 0.54(p<0.001). The results showed that increased illness perception in MS patients improves their physical health. Therefore, we can improve MS patients’ physical health-related quality of life through peer support groups and hence promote patients’ quality of life.